2009
DOI: 10.1371/journal.pone.0008322
|View full text |Cite
|
Sign up to set email alerts
|

Hypothalamic Sirt1 Regulates Food Intake in a Rodent Model System

Abstract: Sirt1 is an evolutionarily conserved NAD+ dependent deacetylase involved in a wide range of processes including cellular differentiation, apoptosis, as well as metabolism, and aging. In this study, we investigated the role of hypothalamic Sirt1 in energy balance. Pharmacological inhibition or siRNA mediated knock down of hypothalamic Sirt1 showed to decrease food intake and body weight gain. Central administration of a specific melanocortin antagonist, SHU9119, reversed the anorectic effect of hypothalamic Sir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
181
2
4

Year Published

2012
2012
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 183 publications
(194 citation statements)
references
References 52 publications
7
181
2
4
Order By: Relevance
“…However, the mechanism underlying the regulation of SIRT1 protein content by TH is not clear, and the unchanged steady levels of Sirt1 mRNA do not support a transcriptional mechanism. Other reports had demonstrated altered levels of the protein in the presence of unchanged Sirt1 mRNA expression (Kanfi et al 2008, Cakir et al 2009, and post-transcriptional and post-translational mechanisms have been shown to be involved (Zschoernig & Mahlknecht 2008, Gao et al 2011. However, in our study, we are not able to exclude the possibility that Sirt1 mRNA level might have preceded the significant increase in SIRT1 protein, as we did the analysis just by the end of the hypo-and hyperthyroidism induction protocols.…”
Section: Sirt1 Regulation By Th Involves Trbmentioning
confidence: 56%
“…However, the mechanism underlying the regulation of SIRT1 protein content by TH is not clear, and the unchanged steady levels of Sirt1 mRNA do not support a transcriptional mechanism. Other reports had demonstrated altered levels of the protein in the presence of unchanged Sirt1 mRNA expression (Kanfi et al 2008, Cakir et al 2009, and post-transcriptional and post-translational mechanisms have been shown to be involved (Zschoernig & Mahlknecht 2008, Gao et al 2011. However, in our study, we are not able to exclude the possibility that Sirt1 mRNA level might have preceded the significant increase in SIRT1 protein, as we did the analysis just by the end of the hypo-and hyperthyroidism induction protocols.…”
Section: Sirt1 Regulation By Th Involves Trbmentioning
confidence: 56%
“…No SNPs were found in the coding sequence from the set of animals used in this study. SNPs g.-382G > A and g.-274C > G were located in the promoter region and could cause disruption of several transcription factor binding sites, as predicted by MatInspector release 8.0 (Cakir et al, 2009). The other three SNPs were found in intron five.…”
Section: Identification Of Snpsmentioning
confidence: 99%
“…In contrast, both intracerebroventricular (i.c.v.) injection of EX-527, a specific Sirt1 inhibitor, and deletion of Sirt1 in Agouti-related peptide (AgRP) neurons (situated adjacent to POMC cells in the hypothalamic arcuate nucleus (ARC), cause decreases of food intake and body weight in mice and rats (8,9). Thus, it appears that Sirt1 in different neuronal populations may play distinctive and sometimes even opposing roles in energy balance regulation.…”
Section: Sirt1 Is a Nadmentioning
confidence: 99%